Placemaking, livability and public spaces: Achieving sustainability through eco-liv@ble design. - Sepe, Marichela (Springer, 2018)
The livability of places is determined by many factors which are in turn influenced by a variety of tangible and intangible elements concerning the area in question and its surrounding. At the same time, computer science and new technologies have in recent decades become increasingly useful supports for the improvement of studies and applications in the field of area investigations. Consequently, the theory of placemaking has been updated and new methods and representational tools have been developed in order to make it capable of illustrating more complex urban scenes and help provide urban sustainability. One of these is the original Ecoliv@ble design method which consists of different kind of surveys, observations and questionnaires. The aim of this paper is to present the Ecoliv@ble design method which intended to: identify sustainable urban livability and the factors which make places happy and livable from the users' point of view; and identify design interventions to enhance or create livability. The method is supported by a software, still in development, for smart phone or multimedia tablet. The final product will be constituted by interactive mosaics capable to visualize places and factors which contribute to urban livability and happiness. The main users to who Ecoliv@ble design method is devoted include visitors, tourists, technicians and administrators who are interested in more liveable and sustainable places. The description of two emblematic case studies conclude the paper.
Keywords: Stadtplanung; Urbanität; Lebensqualität; Gesundheitsförderung; Digitalisierung; Aufenthaltsqualität; Öffentlicher Raum; Park